A visible light promoted O-glycosylation with glycosyl trichloroacetimidates using eosin Y as an organo photoacid. (April 2020) - Liu, Jiao; Yin, Shan; Wang, Haimei; Li, Hongfang; Ni, Guanghui
Abstract: A photoacid catalyzed O -glycosylation of alcohols with glycosyl trichloroacetimidates in the presence of commercially available phenolic photoacids, fluorescein, 4′, 5′-dibromo-fluorescein, and eosin Y under visible light irradiation by blue LEDs was developed. The method is operationally simple without neutralization and proceeds at room temperature. Graphical abstract: Image 1 Highlights: A novel glycosylation method promoted by visible light. Photo catalyst is eosin Y. The donor is glycosyl trichloroacetimidate.